APPLICATION OF SMART PRODUCTION AND DIGITAL EDUCATIONAL MARKETING TO STRENGTHEN THE COMPETITIVENESS OF MOCAF IN KWT GEMILANG II - Andaiyani, Sri; Mavilinda, Hera Febria; Defira, Citra (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Food security is a major challenge for Indonesia, particularly due to its heavy reliance on imported food commodities. In this context, community groups such as the Women Farmers Group (Kelompok Wanita Tani/KWT) play an essential role in supporting local food self-sufficiency. This Community Service Program (PKM) under the Community Partnership Empowerment scheme was implemented with KWT Gemilang II in Palembang to improve the added value and competitiveness of mocaf flour as a local substitute for wheat. The program emphasized three aspects: enhancing production capacity, strengthening business management, and optimizing branding and digital marketing. Activities included training on digital business adoption, promotional content creation, and educational content marketing to raise consumer awareness of healthy local food. Smart production practices were introduced to increase efficiency and hygiene through the use of modern equipment such as sealers, ovens, mixers, and blenders. Branding and packaging improvements were also carried out, including logo, label, and design development aligned with the values of local food innovation. The results show improved knowledge of efficient and hygienic production, stronger brand identity, better digital marketing skills, and more professional packaging. Digital outreach has expanded through Instagram, WhatsApp Business, and Shopee. These achievements are expected to enhance competitiveness, strengthen local economic independence, and contribute to food security in South Sumatra.